Well-being and comfort (Ingeniería, Sostenibilidad y Sociedad, 2020)
Our project is based on the design and implementation of a grid-connected photovoltaic power generation system (SIN). By conducting a feasibility study, we will be able to meet the electrical needs and implement the current RETIE regulations in the facilities to be built, as well as achieve savings throughout the useful life of the installation and its benefits. To carry out the research, we have highly qualified personnel to perform the technical work, which will provide users with greater reliability and peace of mind, as this is a system that is currently being implemented in an unregulated manner. In this way, we are contributing to the sustainability of the environment, as it is a source of clean and friendly energy, allowing for the reduction of CO2 and other greenhouse gas emissions into the atmosphere. It is a 100% safe, harmless, and silent technology, generating greater reliability in its implementation and durability in our homes, contributing to the sustainable development of the city.
Keywords: Photovoltaic systems; energy; clean energy; clean and harmless; regulations; RETIE; reliability